Dental pulp stem cells in endodontic research: a promising tool for tooth tissue engineering - Amit Gandhi; Taru Gandhi; Natasha Madan (Revista Sul-Brasileira de Odontologia, 2012)
Introduction: Millions of teeth are saved each year by root canal therapy. Although current treatment modalities offer high levels of success for many conditions, an ideal form of therapy might consist of regenerative approaches in which diseased or necrotic pulp tissues are removed and replaced with healthy pulp tissue to revitalize teeth. The practice of dentistry is likely to be revolutionized by biological therapies based on growth and differentiation factors that accelerate and/or induce a natural biological regeneration. Literature review: This review summarizes current knowledge, barriers, and challenges in the clinical use of adult stem cells, scaffolds, and growth factors for the development and evaluation of regenerative endodontic therapies.